PENGELOLAAN SUPERVISI PENDIDIKAN DI SMP KECAMATAN KEDAWUNG KABUPATEN SRAGEN - SUKARDI, SUKARDI, Dr. Suyatmini, M.Si, Dr. Darsinah, M. Si (2015)
Sukardi , Q. 100 130 042. Education Management Supervision In SMP Sub District Kedawung Sragen. Thesis, Education Management, Graduate. Universitas Muhammadiyah Surakarta, September, 2015 . The aim of research 1) To describe the supervision of planning education in junior high kedawung District of Sragen. 2) To describe the implementation of educational supervision implemented in the Junior District of kedawung Sragen. 3) To describe the evaluation of educational supervision in the Junior District of Sragen kedawung. This study used qualitative methods. Data were collected through interviews, observation and documentation. The validity of the data using credibility. Data were analyzed interactively and continues over time until complete, so the data is saturated. Results of this study are: 1. Planning Supervision of Education in the District Junior kedawung Sragen. In educational supervision planning activities in junior high school principal in the district kedawung evaluating the implementation of supervision in the past year, plan implementation supervision, and to develop the necessary instruments in supervision. 2. Implementation Supervision Education in the District Junior kedawung Sragen. Educational supervision techniques and classical individual or group. To succeed in the implementation of educational supervision conducted by supervisors, the proper techniques are used to achieve the purpose of effective and efficient secar are individually and group. Steps taken in the educational supervision, among others: a. Pre Supervision meetings; b. Implementation Supervision (the implementation of supervision activities in secondary schools in the District kedawung using some of the following techniques: 1) Monitoring, 2) Interview; 3) Study of documents, 4) Questionnaire; 5); 3. Evaluation of Educational Supervision kedawung In SMP District of Sragen. In order to have meaning, the supervision of the overall activities of supervision, the need for an evaluation of the implementation can be done include: a. Post-observation meeting, b. Evaluation Meeting and c. Follow-up activities Keywords: Management, Supervision, Education, Junior School